Steel connection behaviour in frame and floor system at elevated temperature /Noraini Ajit - Noraini, Ajit (2012)
This thesis presents an analytical investigation on the influence of connection on the performance of steel frame structure and floor system under fire conditions. The connections are modeled through the use of Component Based Method. The implementation is undertaken within the advanced finite element program ADAPTIC, which accounts for material and geometric nonlinearities. Data from a compartment fire test of a four-storey composite building conducted in Gurun, Malaysia was adopted for simulation studies. For steel sub-frame, experimental test based on Coimbra Fire Test was used, which cover endplate connections under fire load. Based on the developed and validated numerical model, parametric studies were performed in order to identify parameters affected the performance of connection under elevated temperatures. Several factors are put into consideration to investigate the influence of connections as well as structural response due to temperature effect, geometric consideration, influence of composite slab and load ratio. From the studies carried out, it can be illustrated that the component based methods is one of the economical and faster solutions to study the behaviour of connection at elevated temperature. Comparison between the experimental and Component Based Method results shows that the developed connection model has the capability to predict the resistance and deformation capacity of semi-rigid connections under elevated temperatures with a satisfactory degree of accuracy. It is important to consider the actual connections configurations in assessing the overall structural response, so that in the beginning of designing stage, designer can estimate the capability of overall structure to resist natural fire accident. From the parametric studies, it can be illustrated that parameters related to connections may influence the overall performance of structures. Further studies on the ductility of connections at elevated temperatures are reviewed in order to identify the limitation of rotation capacity of connections under fire.